ENGLISH BLENDED LEARNING: AN ANALYSIS OF INDONESIAN STUDENTS’ PERCEPTION - Aminah Suriaman; Nurgan Tadeko; Konder Manurung; Sriati Usman; Atik Yuliyani (IJEE (Indonesian Journal of English Education), 2022)
ABSTRACTThe study attempted to analyze the students of Tadulako University's perspective toward blended learning instruction in English teaching. The study employed a quantitative approach using a longitudinal survey design. 48 English department students in the fourth and sixth semesters were selected as the sample of the research using a simple random sampling technique. The data were gained through the questionnaire distributed online and the interview in the face-to-face technique. Data have been analyzed descriptively and inferentially using SPSS Program version 21. The results showed that blended learning through Moodle-based Instruction and face-to-face learning in the classroom was a modern way of learning, convenient to learn English anywhere and anytime. According to most of the respondents, blended learning is the way to enhance their self-directed learning. They can understand the subject well through blended learning, and students feel satisfied using blended learning in English Teaching. It could be concluded that blended learning is helpful to apply in English teaching. The results contributed theoretical and practical information and references to practitioners and researchers in this field of study.                                                                                   ABSTRAK         Penelitian ini mencoba untuk menganalisis perspektif mahasiswa Universitas Tadulako terhadap pengajaran blended learning dalam pengajaran bahasa Inggris. Penelitian ini menggunakan pendekatan kuantitatif dengan menggunakan desain survei longitudinal. 48 mahasiswa jurusan Bahasa Inggris semester empat dan enam dipilih sebagai sampel penelitian dengan menggunakan teknik sampel acak secara sederhana. Data diperoleh melalui kuesioner yang disebarkan secara daring dan wawancara dengan teknik tatap muka. Data dianalisis secara deskriptif dan inferensial menggunakan Program SPSS versi 21. Hasil penelitian menunjukkan bahwa blended learning melalui Pembelajaran Berbasis Moodle dan pembelajaran tatap muka di kelas menurut mahasiswa merupakan cara belajar yang modern, nyaman untuk belajar bahasa Inggris dimana saja dan kapan saja. Blended learning menurut sebagian besar responden, adalah cara untuk meningkatkan self-directed mereka dalam belajar, mereka dapat memahami materi pembelajaran dengan baik melalui blended learning, dan siswa merasa puas menggunakan blended learning dalam Pengajaran Bahasa Inggris. Dapat disimpulkan bahwa blended learning berguna untuk diterapkan dalam pengajaran bahasa Inggris. Hasil penelitian ini memberikan kontribusi informasi dan referensi secara teoritis dan praktis kepada para praktisi dan peneliti selanjutnya dalam bidang studi ini.